Free money, but not tax-free: a proposal for the tax treatment of cryptocurrency hard forks - D. Xu (Russian Journal of Economics and Law)
Hard forks. The first tax is levied on the profit made from the receipt of forked coins, and the second tax is levied on the profit made from the disposition of forked coins. At the same time, a concrete proposal is provided for the applicable coin valuation, tax basis, holding period, and tax rate for the two prongs. The proposed framework is closest to the nature of cryptocurrency hard forks and considers various practical concerns, such as the inefficiency of the cryptocurrency market, the indirect possession of forked coins through third-party exchanges, and the fluctuating trading prices of forked coins when determining the valuation, tax basis, and holding period. This proposal not only provides clarity for taxpayers in filing tax returns and fulfilling tax obligations, but it also relieves the potential tax deferral and tax evasion problems that arise after a cryptocurrency hard fork. Practical significance: the main provisions and conclusions of the article can be used in scientific, pedagogical and law enforcement activities when considering the issues related to taxation regime of cryptocurrency hard forks.